Perbandingan Karakteristik Fisis Kopi Luwak (Civet coffee) dan Kopi Biasa Jenis Arabika - Megah Aysah Fuferti.Z (PILLAR OF PHYSICS, 2013)
Coffee is one of the most popular beverages in the world is consumed by many people. The purpose of this study was to determine how the physical comparisons civet coffee and regular coffee arabika type. Research carried out by varying the mass density of coffee and container volume, the results obtained from the density value of civet coffee is bigger than the usual coffee, civet coffee density value on the container volume 319.32 is 0.02264 whereas regular coffee is 0.01927, the container volume 509.43 density of civet coffee is 0.02265 whereas regular coffee is 0.01989, the container volume 739.41 density of civet coffee is 0.02292 whereas regular coffee is 0.01999. The results of the specific heat shows that the specific heat value of civet coffee is bigger than the usual coffee, civet coffee specific heat value of 14.28 Kal / ° C, while the value of specific heat of regular coffee 10,08 Kal / ° C. Thermal conductivity value of civet coffee is less than the value of regular coffee conductivity, thermal conductivity value of civet coffee is 0.41x10-4 Kal / cm s ° C while the thermal conductivity value of regular coffee 2.74x10-4 Kal / cm s ° C. Water content of the research results obtained civet coffee is 2.5%, while 3.5% of regular coffee so known that the water content of civet coffee is less than the value of the water content of regular coffee arabica types. Keywords: common Type Arabika Coffee, Civet coffee, Density, Thermal Conductivity, Heat type and water content